Altered Expression of CXCL13 and Its Chemokine Receptor CXCR5 on B Lymphocytes during Active Graves' Orbitopathy. (1st February 2021) - Wan, Shangtao; Lin, Miaoli; Mao, Yuxiang; Chen, Xiaoqing; Liang, Dan
ABSTRACT: Purpose: To characterize the phenotypic abnormalities of peripheral B cells in patients with Graves' orbitopathy (GO) and explore the role of chemokine CXC ligand 13 and its receptor type 5 (CXCL13/CXCR5) in relation to B-cell homeostasis using specific neutralizing antibodies. Methods: Adults with active GO (n = 22), inactive GO (n = 28), and healthy control subjects (n = 28) were included in the study. Peripheral B cells and B-cell subsets were quantified and analyzed for CXCR5 expression by flow cytometry. The serum CXCL13 concentration was measured by enzyme-linked immunosorbent assays. For chemotactic experiments, Transwell plates were used, and migrating B cells were further analyzed by flow cytometry. Results: Compared to healthy subjects, patients with active GO had a significantly higher number of CD19 + B cells and the CD19 + CD27 + memory B-cell subset (P = .041 and P = .019, respectively), whereas a marginal increase in the number of these cells was found in patients with inactive GO (P = .062 and P = .087, respectively). Serum CXCL13 levels were significantly higher in patients with active GO (86.9 ± 30.4 pg/mL) than in those with inactive GO (41.7 ± 18.1 pg/mL; P < .001) and in healthy subjects (36.2 ± 7.8 pg/mL; P < .001). The increased CXCL13 concentration was positively and significantly correlated with the clinical activity score (r = 0.757, P < .001). Finally, serum from patients with active GO exerted a stronger chemotactic activity towards B cells and the CD19 + CD27 + memory B-cell subset. Blocking CXCL13 or CXCR5 with neutralizing antibodies reduced B-cell migration by a mean of 20%. Conclusions: Our data suggest that aberrant CXCL13/CXCR5 expression may contribute to the deficits in B-lymphocyte homeostasis observed in active GO.